2015
DOI: 10.5535/arm.2015.39.1.81
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dual-Task Training on Balance and Cognition in Patients With Subacute Post-Stroke

Abstract: ObjectiveTo investigate the effect of dual-task training on the recovery of balance ability and cognitive function in patients with subacute stroke.MethodsTwenty patients (12 males and eight females; average age, 59.70 years) with subacute stroke were enrolled in this study. All participants were randomly assigned to one of two groups, the dual-task group (n=10) or the control group (n=10). The dual task was simultaneous balance and cognitive training using the BioRescue. All patients were evaluated with postu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 25 publications
4
63
1
5
Order By: Relevance
“…Data from the included studies are summarized in Table 1. Of the 42 studies, three were RCTs,3436 and 39 were CCTs. Eight studies evaluated the effects of dual-task training on postural stability 3436,48,61–64.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Data from the included studies are summarized in Table 1. Of the 42 studies, three were RCTs,3436 and 39 were CCTs. Eight studies evaluated the effects of dual-task training on postural stability 3436,48,61–64.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 42 studies, three were RCTs,3436 and 39 were CCTs. Eight studies evaluated the effects of dual-task training on postural stability 3436,48,61–64. Eight studies evaluated the effects of dual tasks on participants suffering from neurological diseases, such as degenerative cerebellar disorder, Parkinson’s disease, and multiple sclerosis 21,65,66.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature in [6] indicated that static balance test standing for 10 seconds with posture stability using force plate had the retest reliability, and the offset trajectories of center of pressure (COP) could be used to effectively detect and quantify postural control parameters, and then to identify static balance performance. The balance test equipment is required to connect laptop to display COP of left or right foot [7], [8]. In the meantime, students' physical conditions including height, weight, leg length and footprint area are recorded in Excel.…”
Section: Methodsmentioning
confidence: 99%